Alcohol Consumption and Trait Anger Strengthen the Association Between Perceived Quarrelsomeness and Quarrelsome Behavior via Feeling Angry. (25th May 2018) - Sadikaj, Gentiana; Moskowitz, D. S.
Abstract : Background: Alcohol intoxication facilitates interpersonal aggression, but this effect depends on person and situation characteristics. Using the Alcohol Myopia Model, we examined the joint influence of alcohol, trait anger, and state anger on the association between perceived quarrelsomeness in an interaction partner and quarrelsome behavior in naturally occurring interpersonal interactions. Methods: Using an event‐contingent recording method over a 20‐day period, community adults reported their perception of an interaction partner's quarrelsome behavior, their own anger and quarrelsome behavior, and the number of alcohol drinks consumed up to 3 hours prior to an interpersonal interaction. Results: Results revealed that alcohol consumption and trait anger jointly moderated the association between perceived quarrelsomeness and quarrelsome behavior indirectly via state anger. Heightened anger experience accounted for increased quarrelsome behavior in response to perceived quarrelsomeness among higher trait anger individuals who reported increased alcohol consumption. When no alcohol was consumed, no such difference in quarrelsome behavioral response was found between low and high trait anger individuals. Conclusions: Findings suggest that alcohol consumption may strengthen the influence of perceived quarrelsomeness on a person's own quarrelsome behavior among individuals with a readiness to experience anger. Intense anger experience may undermine these individuals' ability to inhibit aggressive behaviors when under the influence of alcohol. Abstract : In naturally‐occurring social interactions, we examined whether alcohol consumption and trait anger moderated the influence of perception of quarrelsomeness on a person's anger and quarrelsome behavior. Participants recorded their perception of an interaction partner's quarrelsomeness, their anger and their quarrelsome behavior, and the number of alcohol beverages consumed prior to and during a social interaction. Drinking increased the influence of perceived quarrelsomeness on quarrelsome behavior among high trait anger individuals, in part because of the intense anger experienced. Hypothesized model of alcohol and trait anger jointly moderating the direct and indirect associations of perceived quarrelsome behavior and quarrelsome behavior via anger.